Sleep in Psychotic Disorders: Results From Nationwide SUPER Finland Study - Cederlöf Erik; Holm Minna; Lähteenvuo Markku; Haaki Willehard; Hietala Jarmo; Häkkinen Katja; Isometsä Erkki; Jukuri Tuomas; Kajanne Risto; Kampman Olli; Kieseppä Tuula; Lahdensuo Kaisla; et al. (Oxford University Press, 2022)
Objective
Characterizing sleep in patients with schizophrenia, schizoaffective disorder, bipolar disorder, and psychotic depression.
Methods
This cross-sectional questionnaire study is based on the SUPER study sample, which is part of the Stanley Global Neuropsychiatric Genomics Initiative. The study is a multicentre, nationwide Finnish study consisting of patients (N = 8 623) both in primary and specialized health care. The main measurements were sleep duration, difficulties initiating sleep, early morning awakenings, and fatigue. These results were compared with a nationally representative sample of the Finnish population from the Health 2000 survey (N = 7 167) with frequency and logistic regression analyses.
Results
Patients had more sleep problems compared with the general population, especially young and middle-aged patients (Difficulties initiating sleep in young patients odds ratio = 12.3, 95% CI 9.8–15.4). Long sleep duration was the most deviating property of the sleep characteristics, being particularly common among young patients with schizophrenia (odds ratio = 27.9, 95% CI 22.1–35.2, 47.4% vs 3.3% prevalence). All sleep problems were associated with worse subjective health. We also conducted a latent class analysis, resulting in a cluster relatively free of sleep problems (58% of patients), an insomnia symptom cluster (26%), and a hypersomnia symptom cluster (15%).
Conclusions
In our sample, patients with psychotic disorders have more sleep problems—especially long sleep duration but also insomnia symptoms—compared with the general population. The patients can in a latent class analysis of their sleep symptoms be divided into groups with differing sleep profiles.